Calcitonin Promotes Mouse Pre‐implantation Development: Involvement of Calcium Mobilization and P38 Mitogen‐Activated Protein Kinase Activation. Issue 3 (8th May 2013) - Wang, F‐w; Zhang, Y‐m; Wang, Z; Liu, S‐m; Wang, L‐y; Zhang, X‐l; Jia, D‐y; Hao, A‐j; Wu, Y‐l
Contents: The study was designed to examine the effects of calcitonin (CT) on the development of murine pre‐implantation embryos and possible molecular mechanisms involved in the process. In the present study, the 2‐cell embryos were treated with different concentration of CT in vitro for the indicated time and the results demonstrated that CT promoted the development of the pre‐implantation embryos in a dosage‐dependent manner by increasing the intracellular Ca 2+ level. Furthermore, the present study showed that CT significantly increased the expression of phospho‐P38MAPK (Mitogen‐Activated Protein Kinase) of the pre‐implantation embryos by Western blots and pre‐treatment of specific P38MAPK inhibitor significantly reduced the promotion effects of CT on the embryonic development in vitro culture. Moreover, the results of intrauterine horn injection showed that the average number of embryos implanted in CT‐antibody or specific P38 MAPK inhibitor‐treated uterus was significantly lower than that of the corresponding control, respectively. And the observation of tissue specimen suggested that some embryos were degenerated in CT‐antibody or specific P38 MAPK inhibitor‐treated uterus, and adipose vacuoles were present in the decidual cells. In conclusion, CT promoted the development of pre‐implantation embryos and the intracellular Ca 2+ ‐dependent P38MAPK signal molecule was involved in the process.